STRATEGI PENGUMPULAN DATA DALAM PENELITIAN KUALITATIF: TEKNIK, TANTANGAN DAN SOLUSINYA - Nur Intifada Zahroh; Lusy Amelia Nasution; Aulia Dzulfa Tazqia; Haura Adzra Intan Faiha; Delvina Nurhayati (TARBIYATUL ILMU: JURNAL KAJIAN PENDIDIKAN, 2025)
Qualitative research plays a very important role in finding data, understanding a phenomenon, experience, and seeking information in depth. This article aims to review data collection strategies in qualitative research, especially the techniques used, challenges faced, and solutions that can be applied. One of the main issues discussed is how researchers can choose the right data collection method and overcome challenges that arise during the process, such as difficulty in accessing participants, subjectivity, ethics, and time/location limitations. The method used in writing this article is a literature study, namely by reviewing various sources of books, journals, scientific articles and previous relevant research results. The results of the study show that the most frequently used methods in qualitative research are in-depth interviews, participant observation, documentation, and Focus Group Discussions (FGD). However, each technique has its own constraints, so researchers need to have a strategy and adjust the techniques used to the objectives and field conditions in their use. By understanding the problems and their solutions, researchers can obtain clearer and more relevant research results, so that they can improve the quality of the data collected.